IMPLEMENTASI JARINGAN SARAF TIRUAN UNTUK MEMPREDIKSI TINGKAT PRODUKSI JAGUNG GILING MENGGUNAKAN METODE BACKPROPAGATION (STUDI KASUS: MIKRA MAKMUR BERSAMA) - Aritonang, Reza Sri Rezeki; Saputra, Imam; Siregar, Annisa Fadillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to implement Artificial Neural Networks (ANN) to predict corn flour production levels at the agricultural company Mikra Makmur Bersama using the backpropagation learning method. As a machine learning technique, ANN has the potential to enhance prediction accuracy by effectively analyzing historical data. Data on corn flour production from 2021 to 2023 was collected from the company and used to train the ANN model with a backpropagation architecture. This process involves feedforward and backward propagation to optimize neuron weights, aiming to produce accurate and reliable predictions. The backpropagation algorithm updates weights based on prediction errors and can adapt to complex patterns in the data. The results show that the implemented ANN model successfully predicted corn flour production levels with significant accuracy, as tested with data from 2021 to 2023. This study is expected to serve as a reference for applying ANN technology in other agricultural sectors and encourage the use of advanced methods to enhance efficiency and productivity.